Sex-biased adaptive immune regulation in cancer development and therapy - Johanna M. Schafer; Tong Xiao; Hyunwoo Kwon; Katharine Collier; Yuzhou Chang; Hany Abdel-Hafiz; Chelsea Bolyard; Dongjun Chung; Yuanquan Yang; Debasish Sundi; Qin Ma; Dan Theodorescu; et al. (iScience, 2022)
Summary: The cancer research field is finally starting to unravel the mystery behind why males have a higher incidence and mortality rate than females for nearly all cancer types of the non-reproductive systems. Here, we explain how sex – specifically sex chromosomes and sex hormones – drives differential adaptive immunity across immune-related disease states including cancer, and why males are consequently more predisposed to tumor development. We highlight emerging data on the roles of cell-intrinsic androgen receptors in driving CD8+ T cell dysfunction or exhaustion in the tumor microenvironment and summarize ongoing clinical efforts to determine the impact of androgen blockade on cancer immunotherapy. Finally, we outline a framework for future research in cancer biology and immuno-oncology, underscoring the importance of a holistic research approach to understanding the mechanisms of sex dimorphisms in cancer, so sex will be considered as an imperative factor for guiding treatment decisions in the future.